Nano Titanium(IV) Oxide Modified Carbon Paste Electrode for Analysis of Butylated Hydroxytoluene Concentration in Lotion by Cyclic Voltammetry - Rosyiidah, Nur Anisa; Setiarso, Pirim (Indonesian Journal of Chemistry, 2025)
This research focuses on the manufacture and application of TiO2 NPs modified carbon paste electrodes (TiO2 NPs-CPE) to analyze butylated hydroxytoluene (BHT) concentration in lotions by cyclic voltammetry. This study aimed to determine the best composition of TiO2 NPs-CPE, optimal addition of phosphate buffer pH, application of deposition time, and optimal scan rate by cyclic voltammetry. BHT solution was used to determine the electrode with the best conditions so that an optimal voltammogram was obtained at a composition of 3:5:2 electrode (carbon:TiO2 NPs:paraffin oil), phosphate buffer pH 8, deposition time of 25 s, and scan rate of 100 mV s−1. Obtaining BHT levels of samples A, B, and C with TiO2 NPs-CPE by cyclic voltammetry were 0.4686, 0.48029, and 0.39044%, while the concentration of samples in HPLC were 0.46873, 0.48111, and 0.39191%. A significance value of 0.985 (> 0.05) was obtained, meaning there was no significant difference in the results of measuring the concentration of BHT in the lotion samples.